The The Teachers' Perception towards the Use of Google Translate as a Translation Tool - Andari, Alviola Zhafirah; Sofyan, Rudy; Yusuf, Muhammad (Politeknik Harapan Bangsa Surakarta, 2022)
This study aims to determine teachers' perceptions of the use of Google Translate as a translation tool. The problem of this study is to explain the teachers' perception towards the use of Google Translate as a translation tool. This study uses qualitative descriptive as the research method. The data of this study uses Questionnaire and Interview. The subject is the teachers at Hikmatul Fadhillah and there are 23 teachers. The results of this research showed that teachers can get translation results quickly and easily from Google translate. Almost all teachers realize that Google translate as a translation tool could not be a good tool because the grammar of the translation results is inappropriate. Although this application has weaknesses, teachers still have a positive perception of its use. It is found that all respondents stated they had positive perceptions towards the use of Google translate as a translation tool. Furthermore, the accuracy of Google Translate makes teachers continue to learn and practice grammar while also increasing their translation skills.